Strawberry tree honey as a new potential functional food. Part 1: Strawberry tree honey reduces colon cancer cell proliferation and colony formation ability, inhibits cell cycle and promotes apoptosis by regulating EGFR and MAPKs signaling pathways. (June 2019) - Afrin, Sadia; Giampieri, Francesca; Cianciosi, Danila; Pistollato, Francesca; Ansary, Johura; Pacetti, Mattia; Amici, Adolfo; Reboredo-Rodríguez, Patricia; Simal-Gandara, Jesus; Quiles, Josè L.; Forbes-Hernández, Tamara Y.; Battino, Maurizio
Graphical abstract: Highlights: SHT inhibits colon cancer cells proliferation and colony formation ability. STH arrests cell cycle at S and G2/M phase by regulating cell cycle-related genes. SHT promotes apoptosis, activating both intrinsic and extrinsic pathways. SHT modulates EGFR and MAPK pathways inducing cancer cells death. Abstract: The aim of this work was to assess the phytochemical composition and anticancer effects of Strawberry-tree honey (STH) on cellular proliferation, cell cycle and apoptosis in human colon adenocarcinoma (HCT-116) and metastatic (LoVo) cancer cells. Kaempferol and gallic acid were the major phenolic compounds. STH showed higher cytotoxic and anti-colonogenic effects in a time- and dose-dependent manner; it arrested cell cycle in S and G2/M and regulated cell cycle genes, such as cyclin D1, cyclin E, CDK2, CDK4, p21Cip, p27Kip and p-RB. STH treatment promoted apoptosis by modulating key genes (p53, caspase-3, c-PARP) as well as intrinsic (Bax/Bcl2, Cyto C and caspase-9) and extrinsic (Fas L and caspase-8) apoptotic factors. STH also caused endoplasmic reticulum stress by increasing ATF-6 and XBP-1 expressions, suppressed EGFR, HER2 and downstream markers (p-Akt and p-mTOR) and elevated p-p38MAPK and p-ERK1/2. In conclusion, STH have shown a chemo-preventive action on different colon cancer cell models.